Standarisasi Penilaian Soft competency untuk Posisi Management trainee dan Supervisor pada PT. X. - Aldy Kosasih; Herry Palit (Jurnal Titra, 2023)
PT. X has a guideline about the assessment system for soft competencies for management trainee and supervisors, but the guideline reveals several overlapping, unclear competencies and behaviors that impact the assessment system. The current assessment system lacks accuracy and has difficulties in identifying the root causes of issues. In addition to the overlapping competencies and behaviors, the current assessment has no indicators for each behavior, and the assessment system itself is not good enough, resulting in poor scores. Therefore, this research aims to create a standardization of soft competencies for management trainee and supervisor. The research use expert judgment method to create a new standardization for soft competencies. After the new standard for soft competencies is created, a distribution of forms is conducted, and an analysis is performed by comparing the form assessments with the general assessments. The average score obtained is 3.8 points, with a range of differences between the form assessments and the general assessments from 0.1 to 12.58 points. It is found that 61.5% of the priority competencies need improvement in terms of accuracy. As a result, concluded that the newly standard soft competency cannot be implemented yet due to insufficient data and inadequate analysis results.